Anisimova A. A. Specific peculiarities of the grammatical skills formation for speaking German after English of future interpreters - Anisimova A. A. (Philological Treatises, 2020)
The article is devoted to the problem of formation of grammatical skills for speaking German (as a second foreign language after English) of future interpreters. The author of the article mentions that the efficiency of the educational process of learning the second foreign language can be achieved at the expense of the taking into account specificity of grammatical skills for speaking German as a second foreign language.